The Long Tail Theory in the fashion market: Contributions to the development of a Product-Service System Proposal (ModaPalavra e-periódico, 2025)
The aim of this article is to contextualize elements of the Long Tail Theory and the concepts of the Product-Service System (PSS) in order to compose a PSS proposal that meets a perceived demand in the plus size women’s clothing niche. This research used the inductive method, with an applied purpose and qualitative data analysis. Among the technical procedures, the bibliographical research was based on a systematic review of the literature. The result was a comparative table of these fundamentals, which served as a basis for the PSS proposal.
Keywords: long tail theory; product-service system; clothing